Pengaruh Persalinan Abnormal Terhadap Morbiditas dan Mortalitas Janin dan Usaha Menurunkan Kematian Perinatal - Risanto Siswosudarmo, Risanto Siswosudarmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
A discussion of the impact -of abnormal labor on the neonatal morbidity and mortality with special reference to birth trauma and perinatal mortality has been carried out. This report is a literature review of cases found in Sardjito Hospital and an illustration of obstetric cases during the first semester of 1987. The aim of this paper is to find out how far the negative impact of abhor.. LI labor on birth trauma and perinatal mortality is, as well as preventive measures to be taken.It is obvious that abnormal vaginal deliveries give rise to an increase incidence of birth trauma compared to spontaneous deliveries. The higher the birth weight, the higher the incidence of birth trauma. Caput succedaneum is the most frequent type of birth trauma. whereas broken bone is the least frequent.Transverse position is the most unfavorable position of the fetus, giving the perinatal mortality rate (PMR) 775/1000 deliveries. The second one is breech presentation, having the PMR 129/1000 deliveries. The very unfavorable obstetric operatives are vacuum and forcipal extraction and internal podalic version which altogether bring about the PMR 210.5/1000 deliveries. Prolonged labor gives rise to the PMR 21/2 times higher compared to non-prolonged labor. Although the Cesarean rate is quite high (12.5%), its PMR is still higher. This signifies that Cesarean section has not been adequately accomplished.Some efforts to reduce the PMR in this hospital are (1) expecting the high risk pregnant women especially during labor to be referred as soon as possible, (2) fast and appropriate management of such cases with sophisticated instruments provided, and (3) providing an intensive neonatal care.Key Words: high risk pregnancy – abnormal labor and delivery birth trauma – perinatal mortality rate – neonatal care